Penggunaan Algoritma Binary Search Pada Aplikasi Kamus Bahasa Teochew - Clesya, Clesya; Hoendarto, Genrawan; Sudjalmo, Sugito (MDP Student Conference, 2025)
The preservation of regional languages, especially the Teochew dialect spoken in Pontianak City, Indonesia. Has been impacted by globalization and technological developments. Because of environmental forces that force them to adopt Indonesian, the younger generation hardly ever employs the Teochew dialect nowadays. The Teochew dialect risks extinction over time if it is not given proper consideration right now. The goal of this project is to create a Teochew digital dictionary application that can be utilized as a learning tool and is anticipated to help conserve the language in order solve these issues. The Binary Search technique was used in the design of the Teochew language dictionary application. By using the Binary Search method, a faster and more efficient word search can be ensured. In order to optimize the Binary Search, the dictionary database used provides essential Teochew language vocabulary that has been organized alphabetically. The test results show the Binary Search algorithm can recognize words more quickly than Sequential Search, so this makes it suitable for dictionary applications that require to find words more efficiently. It is expected that this application would serve as a means of education and aid in the preservation of Teochew culture and language.